Pengaruh Vermikompos dan Trichoderma terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) - Suradi Suradi; Pramono Hadi; Libria Widiastuti (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aimed to evaluate the effect of vermicompost and Trichoderma on the growth and yield of cucumber (Cucumis sativus L.). The experiment was arranged in a factorial Completely Randomized Design (CRD) with two factors. The first factor was vermicompost dose consisting of three levels: V1 (0.25 kg/polybag), V2 (0.50 kg/polybag), and V3 (0.75 kg/polybag). The second factor was Trichoderma dose with three levels: T1 (150 ml/polybag), T2 (200 ml/polybag), and T3 (250 ml/polybag). The results showed that vermicompost significantly affected the number of leaves, number of fruits, and fruit weight. The V1 treatment (0.25 kg/polybag) produced the best vegetative and generative growth. A significant interaction between vermicompost and Trichoderma was observed, where the V1T2 combination resulted in the highest fruit weight (956.67 g). These results indicate that the interaction between vermicompost and Trichoderma improves cucumber growth and yield, and the V1T2 combination is the most effective treatment.